Syk inhibitors protect against microglia-mediated neuronal loss in culture - Birkle, Timothy J. Y.; Brown, Guy C. (Frontiers in Aging Neuroscience, 2023)
Microglia are brain macrophages and play beneficial and/or detrimental roles in many brain pathologies because of their inflammatory and phagocytic activity. Microglial inflammation and phagocytosis are thought to be regulated by spleen tyrosine kinase, Syk, which is activated by multiple microglial receptors, including TREM2 (Triggering Receptor Expressed on Myeloid Cells 2), implicated in neurodegeneration. Here, we have tested whether Syk inhibitors can prevent microglia-dependent neurodegeneration induced by lipopolysaccharide (LPS) in primary neuron-glia cultures. We found that the Syk inhibitors BAY61-3606 and P505-15 (at 1µM and 10µM, respectively) completely prevented the neuronal loss induced by LPS, which was microglia-dependent. Syk inhibition also prevented the spontaneous loss of neurons from older neuron-glia cultures. In the absence of LPS, Syk inhibition depleted microglia from the cultures and induced some microglial death. However, in the presence of LPS, Syk inhibition had relatively little effect on microglial density (reduced by 0-30%) and opposing effects on the release of two pro-inflammatory cytokines (IL-6 decreased by about 45%, TNF increased by 80%). Syk inhibition also had no effect on the morphological transition of microglia exposed to LPS. On the other hand, inhibition of Syk reduced microglial phagocytosis of beads, synapses and neurons. Thus, Syk inhibition in this model is most likely neuroprotective by reducing microglial phagocytosis, however, the reduced microglial density and IL-6 release may also contribute. This work adds to increasing evidence that Syk is a key regulator of the microglial contribution to neurodegenerative disease and suggests that Syk inhibitors may be used to prevent excessive microglial phagocytosis of synapses and neurons.